The Use of Voice Control in 3D Medical Data Visualization Implementation, Legal, and Ethical Issues - Miklos Vincze; Bela Molnar; Miklos Kozlovszky (Information)
Voice-controlled devices are becoming increasingly common in our everyday lives as well as in medicine. Whether it is our smartphones, with voice assistants that make it easier to access functions, or IoT (Internet of Things) devices that let us control certain areas of our home with voice commands using sensors and different communication networks, or even medical robots that can be controlled by a doctor with voice instructions. Over the last decade, systems using voice control have made great progress, both in terms of accuracy of voice processing and usability. The topic of voice control is intertwined with the application of artificial intelligence (AI), as the mapping of spoken commands into written text and their understanding is mostly conducted by some kind of trained AI model. Our research had two objectives. The first was to design and develop a system that enables doctors to evaluate medical data in 3D using voice control. The second was to describe the legal and ethical issues involved in using AI-based solutions for voice control. During our research, we created a voice control module for an existing software called PathoVR, using a model taught by Google to interpret the voice commands given by the user. Our research, presented in this paper, can be divided into two parts. In the first, we have designed and developed a system that allows the user to evaluate 3D pathological medical serial sections using voice commands. In contrast, in the second part of our research, we investigated the legal and ethical issues that may arise when using voice control in the medical field. In our research, we have identified legal and ethical barriers to the use of artificial intelligence in voice control, which need to be answered in order to make this technology part of everyday medicine.